Water Has Memory. Issue 1 (2nd January 2020) - Hallock, Thomas
Abstract : In January 2011, police in St. Petersburg, Florida, raided the home of Hydra Lacy, an African-American man charged with domestic battery. Lacy hid in the tight garret of his one-story house, shots were fired, and Lacy as well as two officers died in the confrontation. The city of St. Petersburg demolished the structure and removed the rubble to the local landfill, before a crime scene investigation could be conducted. The fill sits on a swale, in a mostly African American section of St. Petersburg, near a playground and along a creek where the Aramus guarauna, or limpkin can be found – a bird endemic to Florida and a rare sighting, particularly in a city. This poem uses the principles of structuration to examine silences and gaps in our collective stories of both nature and race.